Role of Wood Preservation in Carbon Locking - Rana, A. K.; Tripathi, Sadhna; Dev, Indra (Indian Forester, 2003)
The green house effect is a widely known phenomenon based on established scientific principles. Human activities like burning of forest fuel , destruction of forests add CO2 to the atmosphere , which enhance the global temperature. This problem requires creative solutions to maintain the balance of ecosystem and check the unnatural climate change. Afforstration and forest fuels replacements are some of the measures to control it. Besides the above , there are natural forces which decay the wood products and add CO2 to the atmosphere. This paper deals with the different aspects of carbon increase , and measures to control it. Carbon storage in wood products may be one of the potential way , which can be achieved by prolonging the life of wood and wood products through adopting wood preservation.